Nutritional status and handgrip strength in elderly living at low human development index community - Queiroz, Bruno M.; Coqueiro, Raildo S.; Schettino, Ludmila; Pereira, Rafael; Fernandes, Marcos H.; Barbosa, Aline R. (Medicina (Ribeirao Preto), 2014)
Design of the study: Epidemiological cross-sectional population-based household study. Objective: To investigate the relationship between anthropometric indicators of nutritional status and muscular strength in community-dwelling elderly with low human development index. Methodology: Elderly (N = 316) residents of a city in Brazil’s Northeast Region were submitted to an interview and a physical evaluation. The dependent variable assessed was handgrip strength. The independent variables were body mass index and arm muscle area. The control variables were age, smoking, physical activity, hospitalization and hyperglycemia. Simple and multiple linear regression models were used for statistical analyses. Results: Following control by adjustment variables, there was significant positive correlation of handgrip strength with body mass index (βadjusted = 0.439; p = 0.010; r2 adjusted = 0.062) and arm muscle area (βadjusted = 0.046; p = 0.003; r2 adjusted = 0.087) for male individuals, but not for female individuals. Conclusions: Anthropometric indicators of nutritional status have been positively related to handgrip strength in elderly men, but not in women.